2013
DOI: 10.17239/l1esll-2013.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Exploring syntactic structures in first-language education: effects on literacy-related achievements

Abstract: A quasi-experimental study with 256 German sixth-grade students examined the effects of exploring syntactic structures on literacy-related achievements. The core feature of the instruction was that students had the opportunity to deal with syntactic structures directly, not mediated by analytic operations. Instruction covered six lessons targeting two types of syntactic contrasts (syntactic category contrasts, noun case contrasts). The results indicate that students profited from the instruction in their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Döhmann (1977) found that the adult students in her intervention groups improved in punctuation as well as in orthographically marking a grammatical morpheme (conjunction dass 'that' versus relative pronoun das 'that'). In the Funke et al (2013) study, grade 6 experimental students made significantly greater gains than the control students in capitalization, with experimental students improving evenly regardless of their starting conditions. No significant difference was found in general spelling.…”
Section: Intervention Studies Aimed At Promoting Linguistic Skillsmentioning
confidence: 88%
See 3 more Smart Citations
“…Döhmann (1977) found that the adult students in her intervention groups improved in punctuation as well as in orthographically marking a grammatical morpheme (conjunction dass 'that' versus relative pronoun das 'that'). In the Funke et al (2013) study, grade 6 experimental students made significantly greater gains than the control students in capitalization, with experimental students improving evenly regardless of their starting conditions. No significant difference was found in general spelling.…”
Section: Intervention Studies Aimed At Promoting Linguistic Skillsmentioning
confidence: 88%
“…The latter have tended to take for granted that because grammar knowledge underlies skillful writing (Heringer, 2000;Hoffmann, 2000) and appropriate reading comprehension (Glinz, 1993;Heringer, 2001), grammar instruction will automatically foster both. In the present chapter, consideration will be given first to studies on the impact of grammar instruction on writing (Klotz, 1996;Scholz, 1975) and to studies on reading (Blatt, Müller & Voss, 2010;Funke, Wieland, Schönenberg & Melzer, 2013;Hohm, 2007;Szubert, 2015; see also Herrmann, 1974;Döhmann, 1977). Subsequently, some findings about the effects of grammar instruction on spelling and punctuation will be compiled.…”
Section: Intervention Studies Aimed At Promoting Linguistic Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…The writer cannot rely on phoneme-grapheme correspondences and needs to consider the syntactic structure in order to mark the syntactic information. To achieve this task, teaching these syntactic markers by focusing on the underlying syntactic structures has found to be beneficial for children's spelling progress in English (Bryant & Nunes, 2003), French (Bîlici, Ugen, Fayol, & Weth, 2018;Totereau et al, 2013) and German (Funke, Wieland, Schönenberg, & Melzer, 2013;Wahl, Rautenberg, & Helms, 2017). However, the syntactic approach derived from this insight has not TRAINING A SYNTACTIC MARKER 3 found wide-spread use in regular classroom teaching in German-speaking countries.…”
Section: Syntactic Markersmentioning
confidence: 99%